Study on Welding Properties of QP1500 - Qiang, Kejia (International Journal of Materials Science and Technology Studies, 2026)
With the increasing demand for lightweight and high-strength and toughness materials in the automotive, construction machinery, and other fields, quenched and partitioned (Q&P) steel has become a research hotspot due to its excellent strength-ductility matching characteristics [1]. QP1500 high-strength quenched and partitioned steel undergoes welding processing in engineering applications, and the welding method significantly affects its microstructural stability and resistance to hydrogen embrittlement, which is crucial for the safety of component service [2]. This study takes QP1500 steel as the object to explore its microstructure and mechanical properties, focusing on analyzing the regulation of microstructural evolution and hydrogen embrittlement sensitivity by tailor welding and L-bend welding [3]. By combining microscopic analysis methods such as optical microscopy (OM) and scanning electron microscopy (SEM) with tensile testing, slow strain rate testing (SSRT), and hydrogen permeation testing, the process-microstructure-property correlation is revealed. The results show that high power promotes martensitic grain refinement, enhancing tensile strength and elongation. The hardness of the welding start, middle, and end surfaces exhibits the same trend. The end surface hardness is relatively high, showing a gradual upward trend. The hardness of the welding start surface is the lowest. This study provides theoretical and technical support for the optimization of engineering welding processes and hydrogen embrittlement resistance design of QP1500 steel, which is of great significance for promoting the industrial application of high-strength Q&P steel [4].